2021
DOI: 10.1016/j.trip.2021.100333
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and social distancing: Disparities in mobility adaptation between income groups

Abstract: Graphical abstract

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 32 publications
(35 reference statements)
2
30
1
1
Order By: Relevance
“…In Brazil, people with high income were more likely to be able to afford a costly international trip to countries like Italy at the beginning of COVID-19, leading to higher infection rates in high-income areas ( de Magalhaes et al, 2020 ). However, a study in Texas suggested that people with higher income have less outdoor mobility than lower-income individuals, thus they have a lower rate of contracting the coronavirus ( Iio et al, 2021 ). Secondly, the physical condition of people, combining the interactions of age, race and comorbidity, is crucial for identifying COVID-19 vulnerable groups ( Calderon-Larranaga et al, 2020 ) .…”
Section: Resultsmentioning
confidence: 99%
“…In Brazil, people with high income were more likely to be able to afford a costly international trip to countries like Italy at the beginning of COVID-19, leading to higher infection rates in high-income areas ( de Magalhaes et al, 2020 ). However, a study in Texas suggested that people with higher income have less outdoor mobility than lower-income individuals, thus they have a lower rate of contracting the coronavirus ( Iio et al, 2021 ). Secondly, the physical condition of people, combining the interactions of age, race and comorbidity, is crucial for identifying COVID-19 vulnerable groups ( Calderon-Larranaga et al, 2020 ) .…”
Section: Resultsmentioning
confidence: 99%
“…By 19 August 2021, 209,201,939 cases and 4,390,467 deaths had been confirmed worldwide ( WHO, 2021 ). The COVID-19 crisis has resulted in a range of policies and measures aimed at controlling the virus, such as lockdowns, social distancing, school closures and quarantining, severely restricting travel and many other activities globally ( Budd and Ison, 2020 , De Vos, 2020 , Dzisi and Dei, 2020 , Ferguson et al, 2020 , Iio et al, 2021 , Kim, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Caselli, 2019 , Andersen et al, 2020 , Barari et al, 2021 , Gouin et al, 2021 , Coroiu et al, 2020 , Gualda et al, 2021 , Park et al, 2020 , Clark et al, 2020 , Smith et al, 2020 , Al Zabadi et al, 2021 , Papageorge et al, 2021 , Iio et al, 2021 , Watanabe and Yabu, 2021 .…”
Section: Uncited Referencesmentioning
confidence: 99%